2023
DOI: 10.1109/led.2023.3287887
|View full text |Cite
|
Sign up to set email alerts
|

10-kV Ga2O3 Charge-Balance Schottky Rectifier Operational at 200 °C

Abstract: This work demonstrates a lateral Ga2O3 Schottky barrier diode (SBD) with a breakdown voltage (BV) over 10 kV, the highest BV reported in Ga2O3 devices to date. The 10 kV SBD shows good thermal stability up to 200 o C, which is among the highest operational temperatures reported in multi-kilovolt Ga2O3 devices. The key device design for achieving such high BV is a reduced surface field (RESURF) structure based on the p-type nickel oxide (NiO), which balances the depletion charges in the n-Ga2O3 channel at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In this work, we use an Ar:O 2 flow rate of 20:1. The N A of NiO is extracted to be 1.3×10 18 cm -3 from the C-V data of a p-NiO/n + -Ga 2 O 3 diode similar to [17]. When temperature increases from 25 o C to 125 o C, N A shows an increase by 2.5%, while N D shows nearly no change.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this work, we use an Ar:O 2 flow rate of 20:1. The N A of NiO is extracted to be 1.3×10 18 cm -3 from the C-V data of a p-NiO/n + -Ga 2 O 3 diode similar to [17]. When temperature increases from 25 o C to 125 o C, N A shows an increase by 2.5%, while N D shows nearly no change.…”
Section: Introductionmentioning
confidence: 88%
“…The sample is then dipped into 1:10 BOE for 40 s to produce an undercut on the SiO 2 sidewall. NiO is deposited by magnetron sputtering under the 60/3 sccm Ar/O 2 flow rate with other conditions identical to [17]. The undercut leaves the SiO 2 sidewall un-covered by NiO.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates charge balance at the heterojunction, reducing electric field crowding and enhancing the device's high-voltage-handling capabilities. NiOx-based JTEs [56,62,68], guard rings [69], and reduced surface field structures (RESURFs) [70,71] have In addition to p-n junctions, NiO x can serve as a material for edge termination in β-Ga 2 O 3 devices. This facilitates charge balance at the heterojunction, reducing electric field crowding and enhancing the device's high-voltage-handling capabilities.…”
Section: P-nio X /β-Ga 2 O 3 Heterojunctionmentioning
confidence: 99%
“…This facilitates charge balance at the heterojunction, reducing electric field crowding and enhancing the device's high-voltage-handling capabilities. NiO x -based JTEs [56,62,68], guard rings [69], and reduced surface field structures (RESURFs) [70,71] have been reported as edge terminations for β-Ga 2 O 3 devices. Yan et al [56] demonstrated a β-Ga 2 O 3 SBD with NiO x heterojunction edge termination and a SiO 2 FP structure (Figure 5a).…”
Section: P-nio X /β-Ga 2 O 3 Heterojunctionmentioning
confidence: 99%
“…Compared to GaN and SiC, β-Ga 2 O 3 demonstrates an advantage of large-area single crystal growth by melting methods such as edge-defined film-fed (EFG) [8] or Czochralski [9] method. Although high Hall mobility and power devices have been achieved by homoepitaxially-grown β-Ga 2 O 3 films on (010) β-Ga 2 O 3 substrates [10][11][12][13][14][15][16], the high cost and immature processing technique of the large-size single crystal substrates have hindered the widespread application of the β-Ga 2 O 3 devices. Recently, heteroepitaxial growth of n-doped β-Ga 2 O 3 thin films on cost-effective substrates like sapphire has attracted much attention for the advancement in the Ga 2 O 3 industry.…”
Section: Introductionmentioning
confidence: 99%